FINANCIAL HARDSHIP AND DIETARY ADHERENCE DURING COVID-19 PANDEMIC - Mohd Shukri, Nor Azwani; Sarah Muneera Karami (Malaysian Journal of Public Health Medicine, 2023)
The COVID-19 pandemic affected the global economy resulting in financial hardship due to declining wages or job losses. A decreased income influences food expenditure and accessibility affecting dietary adherence to healthy recommendations. Thus, this study aimed to investigate the association between financial hardship and dietary adherence among Malaysian working adults during the pandemic. Individuals aged 18 to 59 years (N=163) who experienced financial hardship during the pandemic participated in this cross-sectional study. The data were collected through an online survey. The reported number of servings consumed by the respondents for nine food groups was compared with the recommendations by the Malaysian Dietary Guidelines 2020 and Malaysian Food Pyramid 2020 using one-sample t-test to measure dietary adherence. The association between the financial hardship categories (?25%, 26-50%, 51-75%, and 76-100% of monthly household income reduction rate during the pandemic) and dietary adherence status was assessed using the chi-squared test. The respondents consumed significantly lower number of servings of vegetables, fruits, cereals, fish, legumes, milk and milk products, and fat/oils, compared to recommendations (all p<0.001) whereas their sugar intake was significantly higher than recommended (p=0.041). These indicate dietary non-adherence. However, no association between financial hardship and dietary adherence was detected among adults who were financially affected during the COVID-19 pandemic in this study. In conclusion, most Malaysian adults who reportedly experienced financial hardship during the COVID-19 pandemic demonstrated non-adherence to healthy dietary recommendations. However, whether this was influenced by financial difficulties faced during the pandemic is inconclusive and warrants further investigation.